Effect of Using Six Sigma Methodolgy in Improving Quality Control over External Audit in Jordan - Yousef, Ahmad; Thuneibat, Ali (Jordan Journal of Business Administration, 2019)
This study aimed at investigating the effect of using Six Sigma methodology on improving quality control over external audit in Jordan. To achieve the objectives of the study, the researchers designed a questionnaire consisting of (65) paragraphs to gather the primary data from the study sample which consisted of (156) auditors. To analyze data and test the hypotheses of the study, the researchers used descriptive statistics, one-sample T-test, ANOVA and multiple linear regression. The results of the study revealed that all Six Sigma criteria (support for senior leadership, continuous improvement, processes and systems, feedback and measurement and human resources) are of a high level of importance to external auditors in Jordan. The results also showed that all audit quality control elements (ethical requirements, independence, acceptance and continuance of client relationships, assignment of engagement teams and monitoring) are of a high level of importance to external auditing in Jordan. The results also revealed a statistically significant impact of Six Sigma criteria on the elements of quality control over the financial statements’ audit.Based on the results of the study, the researchers suggest many recommendations, including enhancing the skills of external auditors in terms of Six Sigma critera through holding workshops and training courses. The researchers also recommend that audit offices should provide the human, material and technical resources required for the practical application of Six Sigma methodology.